Protodioscin levels in Brachiaria spp. in a sheep production system and a brief review of the literature of Brachiaria spp. poisoning in ruminants - Alberto O. Gaspar; Carolina C. Guizelini; Francisca C. Roberto; Gelson S. Difante; Ricardo C. Brumatti; Camila C.B.F Ítavo; Ricardo A.A. Lemos; Stephen T. Lee (Pesquisa Veterinária Brasileira, 2021)
ABSTRACT: Plants of the genus Brachiaria, used in several countries as forage, are poisonous to some livestock species. Their toxic principle is protodioscin, and the main form of clinical presentation of the toxicosis is hepatogenous photosensitization. Here we compare protodioscin levels in B. decumbens and B. brizantha and review the literature on the concentrations and methodologies of collection and analysis of the toxic principle in Brachiaria spp. and the risk of contamination of pastures by more toxic species that may facilitate poisoning by plants of this genus in sheep. The experiment was conducted in pastures originally formed by B. brizantha, with many B. decumbens invasion points. The occurrence of cases of poisoning by Brachiaria spp. was the criterion for confirming pasture toxicity. The forage samples were collected at ten random points every 28 days through manual grazing simulation. The samples were analyzed for protodioscin by high-performance liquid chromatography (HPLC) with light scattering by evaporation (ELSD) after being dried and crushed. In the flock of 69 sheep, five poisoning cases occurred, three sheep died, and two recovered. The protodioscin levels found in the evaluated pastures ranged from 0.70 to 0.45%; higher levels appeared in B. decumbens (7.09%) compared to 1.04% in B. brizantha. We suggest that Brachiaria spp. should be avoided in pastures where sheep are grazing.